Predator. Badlands [videorecording (DVD)] - Schachner, Sarah; Wallfisch, Benjamin (20th Century Studios, 2026)
Set in the future on a remote planet, a young Predator, outcast from his clan, finds an unlikely ally in Thia and embarks on a treacherous journey in search of the ultimate adversary.